Total Quality Management (TQM) practices: challenges faced by hotel managers / Jazira Anuar, Norzuwana Sumarjan and Salleh Mohd Radzi - Anuar, Jazira; Mohd Radzi, Salleh (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Total Quality Management (TQM) has appeared to be significant in the hotel and tourism industries over the last decades. With the intense competition among organizations in hotel and tourism industries to fulfil customers increasing demand patterns, many organizations have restructure their TQM practices for the betterment of the organization and encounter challenges during the implementation of TQM for maximum benefits. Limited study has addressed issue pertaining to challenges encountered specifically in the service industries. In-depth interviews with eight hotel managers (Human Resource Department) from several hotels in Kuala Terengganu were established. Findings revealed that the challenges encountered from the hotel managers consists of employees' involvement; employees training; top management commitment, product and service designs and quality systems. The managerial implications, recommendations and scope for future study are presented in the end of this paper.